Have you seen Luis Velez? : a novel - Hyde, Catherine Ryan (Lake Union Publishing, 2019)
"Raymond Jaffe feels like he doesn't belong. Not with his mother's new family. Not as a weekend guest with his father and his father's wife. Not at school, where he's an outcast. After his best friend moves away, Raymond has only two real connections: to the feral cat he's tamed and to a blind ninety-two-year-old woman in his building who's introduced herself with a curious question: Have you seen Luis Velez? Mildred Gutermann, a German Jew who narrowly escaped the Holocaust, has been alone since her caretaker disappeared. She turns to Raymond for help, and as he tries to track Luis down, a deep and unexpected friendship blossoms between the two. Despondent at the loss of Luis, Mildred isolates herself further from a neighborhood devolving into bigotry and fear. Determined not to let her give up, Raymond helps her see that for every terrible act the world delivers, there is a mirror image of deep kindness, and Mildred helps Raymond see that there's hope if you have someone to hold on to."--Back cover.